School Policies as a Determinant for Selection of Home Science Subject: The Belvedere of the Kenyan Secondary School - Chelagat, Abigael; Kitainge, Kisilu; Were, Gertrude (African Journal of Education,Science and Technology, 2018)
Home Science is a subject that facilitates acquisition of knowledge, skills and attitudes meant to improve lives of everyone yet very few students choose to pursue it in secondary school. This study sought to establish the influence of school policies on enrolment in Home Science subject in secondary school in 3 Sub-Counties of Elgeyo Marakwet County. It was guided by the following specific objectives: to identify the various school policies on subject selection in secondary schools in Elgeyo Marakwet County and to investigate how school policies on subject selection influenced enrolment of Home Science in secondary schools. The research design adopted was a descriptive survey. Purposive sampling technique was used to select all the six (6) county secondary schools offering Home Science subject at Kenya Certificate of Secondary Education (KCSE) level. This was to ensure a homogenous group for the study with the aim of curbing extraneous variables. Six (6) Home Science teachers were also purposively selected together with the six (6) Principals of all the purposively sampled county secondary schools. This study had a total of twelve (12) respondents. Data from the Home Science teachers was collected using questionnaires and interview schedules were used to collect data from the Principals. The sample size was deemed adequate due to their respective positions in the sampled schools. Data was analyzed descriptively. The study established that most schools did not have policies thus low enrolment in Home Science subject. Also, schools had streaming practices with a class being set specifically for Home Science thus limiting number of students choosing the subject. The study recommends that Home Science related professionals should market the subject through career talks and curriculum developers should review the curriculum for the sake of re-introducing the Home Science subject at primary school for learners to have prior knowledge to undertake the subject at Secondary school. These interventions will increase student enrolment in Home Science subject.
Keywords: ⛔ No DOI found